The Hidden Struggle: Depression Among Seniors - Jabłonowska, Magdalena; Grzeszczuk, Paulina (Quality in Sport, 2025)
Introduction: This review paper aims to provide a comprehensive analysis of the prevalence, underlying determinants, and treatment modalities of depression in older adults, highlighting the roles of both pharmacological and non-pharmacological interventions. Materials and Methods: A comprehensive review of the literature was conducted using the PubMed and Google Scholar databases using the following keywords: "geriatric depression", "late-life depression", "elderly depression", "depression treatment", "psychotherapy", "exercise", "electroconvulsive therapy". Summary: Depression, especially in older adults, is a serious psychiatric disorder characterized by persistent low mood and loss of interest. Despite its high prevalence, it often remains underdiagnosed and undertreated in this age group. Risk factors include chronic illnesses, social isolation, and bereavement, while protective factors involve physical activity, resilience, and social support. Effective management requires a multidisciplinary approach combining pharmacotherapy - primarily SSRIs and SNRIs - with non-pharmacological interventions such as psychotherapy, exercise, and electroconvulsive therapy for severe cases. Regular monitoring and individualized treatment adjustments are essential for improving outcomes in elderly patients with depression. Conclusions: Depression in older adults is a prevalent and frequently underrecognized condition that adversely affects their health and quality of life. Successful management requires a multidisciplinary approach that integrates appropriate pharmacological treatments with nonpharmacological strategies such as psychotherapy and physical activity. Personalized treatment plans and regular monitoring are crucial to achieving better clinical outcomes and reducing the overall burden of depression in the elderly.